Quantitative Evaluation of the Compatibility Effects of Huangqin Decoction on the Treatment of Irinotecan-Induced Gastrointestinal Toxicity Using Untargeted Metabolomics - Cui, Dong-Ni; Wang, Xu; Chen, Jia-Qing; Lv, Bo; Zhang, Pei; Zhang, Wei; Zhang, Zun-Jian; Xu, Feng-Guo (Frontiers in Pharmacology, 2017)
Huangqin decoction (HQD), a traditional Chinese medicine (TCM), has been widely used to treat gastrointestinal syndrome in China for thousands of years. Chemotherapy drug irinotecan (CPT-11) is used clinically to treat various kinds of cancers but limited by its side effects, especially delayed diarrhea. Nowadays, HQD has been proved to be effective in attenuating the intestinal toxicity induced by CPT-11. HQD consists of four medicinal herbs including Scutelleria baicalensis Georgi, Glycyrrhiza uralensis Fisch, Paeonia lactiflora Pall and Ziziphus jujuba Mill. Due to its complexity, the role of each herb and the multi-herb synergistic effects of the formula are poorly understood. In order to quantitatively assess the compatibility effects of HQD, mass spectrometry-based untargeted metabolomics studies were performed. The serum metabolic profiles of rats administered with HQD, single S. baicalensis decoction, S. baicalensis-free decoction and baicalin/baicalein combination were compared. A time-dependent trajectory upon principal component analysis (PCA) was firstly used to visualize the overall differences. Then metabolites deregulation score (MDS) and relative area under the curve (RAUC) were calculated and used as parameters to quantitatively evaluate the compatibility effects of HQD from the aspect of global metabolic profile and the specifically altered metabolites, respectively. The collective results indicated that S. baicalensis played a crucial role in the therapeutic effect of HQD on irinotecan-induced diarrhea. Both HQD and SS decoction regulated glycine, serine and threonine pathway. This study demonstrated that metabolomics was a promising tool to elucidate the compatibility effects of TCM or combinatorial drugs.